The Compilation of Islamic Law as a Socio-Digital Product in the Reform of Islamic Law in Indonesia - M. Doni; Silfia Hanani (Yayasan Lembaga Studi Makwa, 2025)
This study aims to analyze the Compilation of Islamic Law (KHI) as a digital social product reflecting the transformation of Islamic law in Indonesia amidst an increasingly digitized and complex society. It examines how information technology influences the understanding, interpretation, and application of Islamic legal norms contained in the KHI. This study employs a qualitative method with a field research approach, examining the process of drafting the KHI by considering social and digital factors, including public participation and the development of legal discourse. Field research was conducted to explore the implementation of KHI within Indonesia’s religious court system, focusing on the utilization of digital technology to enhance access, transparency, and efficiency in the enforcement of Islamic law. The findings indicate that KHI functions not only as a formal legal document but also as a dynamic social construction that adapts to the needs of contemporary society and technological developments. However, challenges related to the relevance, flexibility, and formal legal status of KHI within the national legal framework still need to be addressed. The study concludes that reformulating KHI as a digital social product is crucial to responding to the modern legal challenges faced by the Indonesian Muslim community, emphasizing the need for adaptive and inclusive regulations. This contribution plays a strategic role for policymakers and legal practitioners to strengthen the role of KHI in building a responsive, participatory, and contextual Islamic legal system in the digital era.